Is Nutritional Screening of Patients with Lung Cancer Optimal? An Expert Opinion Survey of French Physicians and Surgeons. (18th August 2019) - Corbaux, Pauline; Fontaine-Delaruelle, Clara; Souquet, Pierre-Jean; Couraud, Sébastien; Morel, Hugues; Tronc, François; Eker, Elife; Peron, Julien; Raynard, Bruno
Abstract: Objectives: To assess how physicians and surgeons carried out malnutrition screening and follow-up for patients with lung cancer. Materials and methods: We carried out an expert opinion survey in France using an anonymous self-administered online questionnaire. Results: In 2017, 206 practitioners responded, of which 60.7% were pulmonologists, 17.4% thoracic surgeons, 11.2% oncologists, and 10.7% radiotherapists. At initial diagnosis, 79.3% of practitioners recorded patients' percentage of weight loss. During follow-up examinations, 67.5% recorded this data for patients at risk of malnutrition and 70.4 % for malnourished patients. Food intake was evaluated by 21.7% of practitioners at initial diagnosis. Surgeons assessed percentage of weight loss and food intake significantly less often than pulmonologists did, they were less likely to request serum albumin tests and waited for a greater percentage of weight loss before referring patients to a nutrition professional. All practitioners were well aware of the prevalence of malnutrition among lung cancer patients and its consequences. The main factors preventing optimal nutritional assessment reported by practitioners were a lack of time and limited specialized knowledge. Conclusion: Nutritional assessment remained suboptimal, especially for surgical patients. The importance granted to malnutrition needs to be increased for patients with lung cancer, especially in surgical departments. Highlights: Physicians and thoracic surgeons are well aware of the prevalence and consequences in lung cancer patients. Thoracic surgeons seemed to be less sensitized to malnutrition screening than pulmonologists. Lack of time and limited specialized knowledge were reported as the main factors preventing optimal nutritional assessment.